The Influence of Virtual Learning Through Google Meet on Students' Interest in Islamic Education Learning at University - Nurmali'ah, Hiqmah; Arifi, Ahmad; Amir, Abdul Muiz (Scaffolding: Jurnal Pendidikan Islam dan Multikulturalisme, 2023)
Online learning through Google Meet is learning carried out through the Google Meet application, which can be accessed online by lecturers and students. The purpose of this study is: first, to find out virtual learning through Google Meet; second, to find out the learning interests of PAI A students Class of 2021; third, to find out the influence of virtual learning through Google Meet on the learning interest of PAI A students class of 2021 in the ulumul hadith course at IAIN Kendari Southeast Sulawesi. The type of research used is conventional quantification research. The population used by the researcher was 40 PAI A students of the Class of 2021, so the sampling technique in this study used non-probability sampling with 40 saturated samples. The results of the research on the influence of virtual learning through Google Meet on the learning interest of PAI A students class of 2021 in the ulumul hadith course at IAIN Kendari Southeast Sulawesi obtained a significance value of 0.000 < 0.05, so there is a relationship between the two. And when viewed from the degree of relationship, the result is 0.5 84, where the degree of this relationship shows a relationship that is positive and lies in the degree of moderate correlation because 0.584 is at a Person Correlation value of 0.41 to 0.60.